Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT XYZ - Sugiyatno . (JURNAL CITRA WIDYA EDUKASI, 2018)
This research discusses the influence of work motivation and work environment on employee performance in PT XYZ, because basically, motivation and morale of an employee comes from hope that will be obtained. If expectation become reality, then the employee is likely to improve the quality of work. While the work environment will be good will also provide a morale for him. The purpose of the research is to determine the effect of work motivation and work environment on employee performance. This research was conducted at PT XYZ company, Bekasi Regency, West Java. The method used is quantitative descriptive method through survey with multiple linear regression evaluation technique. Data collection was done through questionnaire to all employees, ie 60 people. Employee performance variable is as dependent variable, while work motivation and work environment are as independent variable. Survey result will be tested for validity and reliability. Next will be tested classical assumption as a condition before multiple linear regression analysis. Once declared eligible, then will be done regression testing. The result of research shows that work motivation has a significant effect partially on work performance, while the working environment has no significant partial effect on work performance. However, motivation and work environment have a significant effect simultaneously on employee performance.